A CASA DE NAGÔ CONTINUA VIVA: cuidados e obrigações no Tambor de Mina em São Luís do Maranhão - CARVALHO, Adson Luis Barros de (2024)
This dissertation is about the Casa de Nagô, a Tambor de Mina terreiro, an afro-brazilian religion found in Maranhão. Considered a model for the Tambor de Mina practiced in the state, the Casa was founded at the end of the 18th century. Based on an ethnography carried out at the site in recent years, the dissertation analyses how the place has been constructed in the specialized bibliography on the subject, punctuating the production of its history. In addition, it brings elements of change and continuity that mark the space and the relationship with the entities, discussing the passage of time and the daily ways of maintaining links. This includes the transition of responsibilities from the vodunsis - as the daughters of saints in this religion are called - to the zeladores, who take on the obligations and care of the space and the ritual. Finally, the work suggests the need to understand the various dynamics of updating that keep the Casa de Nagô alive.